2019
DOI: 10.1097/md.0000000000018408
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 gene polymorphisms and susceptibility to liver diseases

Abstract: Background: Several studies have explored the associations between interleukin-6 (IL-6) gene polymorphisms and the susceptibility to liver diseases, however, results remain ambiguous. The goal of this study was to conduct a meta-analysis to provide more credible evidence.Methods: Studies identified in the PubMed, Cochrane Library, and EMBASE databases were used to perform a meta-analysis via the STATA software. Pooled odds ratios (OR) were calculated under fixedand random-effects models to estimate the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…Similarly, a meta-analysis indicated that patients carrying G allele of IL-6 (rs1800795) may be more likely to suffer from liver diseases, which was ethnic-dependent. [ 21 ] Patients carrying IL-6 G allele were found to have high IL-6 expression in plasma and were more likely to cause persistent HCV infection. [ 22 ] In addition, other cytokines such as IL-1α and IFN-inducible protein-10 were also reported to have the potential to be the biomarkers for prognostic of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis indicated that patients carrying G allele of IL-6 (rs1800795) may be more likely to suffer from liver diseases, which was ethnic-dependent. [ 21 ] Patients carrying IL-6 G allele were found to have high IL-6 expression in plasma and were more likely to cause persistent HCV infection. [ 22 ] In addition, other cytokines such as IL-1α and IFN-inducible protein-10 were also reported to have the potential to be the biomarkers for prognostic of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although, several investigations have shown that subjects carrying the GC and CC genotypes of IL-6 SNP had a decreased risk of type 2 diabetes mellitus[ 34 - 38 ], the association has not found by others[ 34 , 39 ], which may be due to the differences in the study designs and/or genetic ancestry of the populations. Concerning the chronic liver diseases, the IL-6-174G/C polymorphism has been associated with both fibrosis progression and hepatocellular carcinoma development[ 41 , 62 , 63 ] in patients with CHC. The majority of the studies has verified an association between the presence of the high producer genotype (GG) and poor outcome in patients with the hepatopathy[ 31 , 32 , 40 , 41 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the chronic liver diseases, the IL-6-174G/C polymorphism has been associated with both fibrosis progression and hepatocellular carcinoma development[ 41 , 62 , 63 ] in patients with CHC. The majority of the studies has verified an association between the presence of the high producer genotype (GG) and poor outcome in patients with the hepatopathy[ 31 , 32 , 40 , 41 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In NAFLD, IL-6 may enhance hepatic repair and regeneration, however, it might also be involved in inducing insulin resistance and stimulating hepatocyte apoptosis, thus contributing to NASH progression (42,44). Indeed IL-6 gene polymorphisms have been associated with an increased susceptibility to chronic liver disease (45).…”
Section: Discussionmentioning
confidence: 99%